2002
DOI: 10.1055/s-2002-28460
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Serum Lipids and Lipoproteins from Childhood to Dyslipidemia in Adults: The Bogalusa Heart Study

Abstract: Our data demonstrate that serum lipid and lipoprotein levels continue to track from childhood into young adulthood. The persistence and clustering of multiple CVD risk factors from childhood to adulthood and the impact of obesity in this regard point to the need for preventive measures aimed at developing healthy lifestyles early in life. Adverse levels of LDL-C in childhood persist over time, progress to adult dyslipidemias, and relate to obesity and hypertension as well. NCEP guidelines which classify CVD ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 7 publications
5
112
3
Order By: Relevance
“…Tracking of serum lipids in Swedish children has not been reported previously, but our results are in agreement with the Finnish STRIP study (Rask-Nissila et al, 2002). Furthermore, tracking of serum lipids from childhood to adulthood was demonstrated by the Bogalusa Heart Study (Nicklas et al, 2002). This supports the importance of early interventions in families with known raised serum lipid levels and known CVD risk (Magnussen et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Tracking of serum lipids in Swedish children has not been reported previously, but our results are in agreement with the Finnish STRIP study (Rask-Nissila et al, 2002). Furthermore, tracking of serum lipids from childhood to adulthood was demonstrated by the Bogalusa Heart Study (Nicklas et al, 2002). This supports the importance of early interventions in families with known raised serum lipid levels and known CVD risk (Magnussen et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…In the study group, which comprised children with a high intake of SAFA and a low intake of PUFA compared with recommended guidelines, TC levels above the cutoffs for abnormal TC (45.2 mmol/l) (Daniels and Greer, 2008) were present in 22% of the children, 49% of the fathers and 32% of the mothers. Furthermore, 24% of the children had LDLC43.35 mmol/l, defined as a risk factor for adult dyslipidemia and associated CVD (Nicklas et al, 2002;Jolliffe and Janssen, 2006). This calculated risk factor in the present study group was four-fold higher compared with the risk factor calculated for the Bogalusa Heart Study (Nicklas et al, 2002).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our data show that parameters frequently associated with risk for the IRS, such as obesity, lipid abnormalities, and fasting insulin, as well as the IRS score itself, track well from pre-to postpuberty in a community sample of both Mexican Americans and non-Hispanic whites. This is consistent with data from the prior longitudinal studies that have reported that BMI (19), insulin (20), serum lipid and lipoprotein (21)(22)(23)(24), and blood pressure (25) levels track longitudinally in children and young adults. An additional finding of this study is that measurements of BMI or waist circumference, triglycerides, and diastolic blood pressure in childhood are relatively strong predictors of the IRS in late adolescence and may help identify those children who are most at risk for the development of diabetes and cardiovascular disease and most likely to benefit from intervention efforts.…”
Section: Statistical Analysessupporting
confidence: 89%
“…9,12,13 Meanwhile, it became increasingly obvious that this lifestyledisease association was already operational in the early stages of life and that risk factors established during childhood have a tendency to track into adulthood and to add to the overall risk profile for chronic diseases. [14][15][16] Considerable attention is therefore given nowadays to the presence of risk factors in children and to start addressing them in preventive campaigns. 17 Against this background, it is of course imperative to have valid comparative frameworks for the interpretation of individual values and population distributions of risk markers like blood lipids.…”
Section: Introductionmentioning
confidence: 99%